Risk factors and outcome of Thai patients with scleroderma renal crisis: a disease duration-matched case control study - Suparaporn Wangkaew (2018)
© 2017 Asia Pacific League of Associations for Rheumatology and John Wiley & Sons Australia, Ltd Introduction: Data regarding the prevalence, risk factors and outcome of scleroderma renal crisis (SRC) in Asian patients with systemic sclerosis (SSc) are limited. Objective: To determine the prevalence, risk factors and outcomes of SRC in Thai SSc patients. Method: Medical records of all SSc patients seen at the Division of Rheumatology, Chiang Mai University, Thailand, from January 1990 to December 2015 were retrospectively reviewed. For each SRC case, a disease duration (±1 year) matched control (four SSc patient without SRC for each SRC patient) was identified. Result: Of 608 SSc patients seen during the study period, 19 SRC cases were identified, resulting in an SRC prevalence of 3.13%, with 76 matched controls. Of the 19 cases, mean ± SD age and median (interquartile range 1–3) disease duration was 56.2 ± 13.8 years and 5 (3–22) months, respectively. Seventeen patients (89.5%) had diffuse cutaneous SSc. Twelve patients (63.2%) had hypertensive renal crisis and seven (36.8%) had normotensive renal crisis. Multivariate conditional logistic regression analyses showed that digital gangrene (adjusted odd ratio [AOR] 31.41, 95% CI = 1.16–852.23, P = 0.041), current prednisolone dose ≥ 15 mg/day (AOR 31.22, 95% CI = 1.59–613.85, P = 0.024), serum albumin < 3 mg/dL (AOR 7.97, 95% CI = 1.49–42.56, P = 0.015), and cardiac involvement (AOR = 6.62, 95% CI = 1.08–40.63, P = 0.041) were independent risk factors for SRC. Fifteen SRC patients (78.9%) required dialysis and 10 (52.6%) died. Conclusion: SRC was an uncommon complication in Thai patients with SSc, but is associated with high mortality. Digital gangrene, current prednisolone dose ≥ 15 mg/day, serum albumin < 3 mg/dL and cardiac involvement were independent risk factors for SRC.